HUBUNGAN POLA ASUH DAN KOMUNIKASI ORANG TUA DENGAN PERKEMBANGAN EMOSIONAL ANAK USIA PRASEKOLAH 3-6 TAHUN DI TK FLAMBOYAN DESA SINDANGKERTA - Indah Fitri Amelia (2021)
The age of 3-6 years is a golden age. actions, behaviors and attitudes of parents affect the development and growth, one of which is the emotional development of the child. Therefore, the selection of parenting and the application of communication to their children need to be considered This research is done to analyze the correlation parenting and communication with the emotional development of preschool-aged children aged 3-6 years in TK Flamboyan Sindangkerta Village. Research design uses quantitative, crosssectional analytics with probability sampling method type random sampling. Data collection using questionnaires through Gform consists of several characteristics of respondents, namely Employment Status, Education Level, Gender of children, Age of parents and Age of Children. Chisquare's alternative analysis test obtained a value of p = 0.000 (<a = 0.05) which means that there is a correlation between parenting and the emotional development of the child. Furthermore, the analysis of communication with emotional development using the T Independent test with a value of p= 0.048 (<a = 0.05) which means there is a correlation between communication and emotional development of children. Suggestions for next researchers to conduct research with a wider population and use quasi-experimental techniques to stimulate a child's emotional development.